Can a combination of nanofat and freeze-dried human amniotic membrane enhance full-thickness wound healing? An animal study using rabbit models - Hidayati, Citra A.; Saputro, Iswinarno D.; Budi, Agus S. (Narra Sains Indonesia, 2024)
Previous studies have explored nanofat stimulating tissue regeneration and maturation, promoting remodeling through its rich content of growth factors and stem cells; however, comprehensive data on its use in full-thickness wounds remains limited. The aim of this study was to evaluate the effectiveness of combining nanofat with freeze-dried human amniotic membrane (FDHAM) for treating full-thickness wounds in a rabbit model. An animal experimental study using a post-test control group design was conducted. Thirty-six male New Zealand white rabbits (Oryctolagus cuniculus) were randomly assigned to two groups: the experimental group (received a combination of nanofat and FDHAM) and the control group (received FDHAM alone). Each group was subdivided to evaluate effects on days 3 and 7. Macroscopic evaluations of wound healing, microscopic assessment of epithelialization and measurement of epidermal growth factor (EGF) levels in the wounds were conducted on days 3 and 7 post-injury. The present study indicated that the combination treatment significantly elevated EGF levels in the wounds on both days 3 and 7 (with p<0.001 for both assessment time points). The combination of nanofat-FDHAM did not significantly accelerate epithelialization on either day 3 or 7. This study highlights that combining nanofat with FDHAM did not significantly speed up epithelialization of full-thickness wounds within the first seven days; however, it notably increased EGF levels, suggesting that nanofat may enhance the wound's biological environment.